2021
DOI: 10.4149/bll_2021_085
|View full text |Cite
|
Sign up to set email alerts
|

Cardiovascular events and atherogenic lipid profile in chronic myeloid leukemia patients treated with nilotinib versus imatinib

Abstract: The aim of this study was to assess cardiotoxicity and potential adverse effects related to lipid metabolism during treatment with tyrosine kinase inhibitors (TKIs) imatinib and nilotinib in patients with chronic myeloid leukemia (CML). PATIENTS AND METHODS: Eighty-two consecutive patients with CML, who received nilotinib and/or imatinib in a single haemato-oncological Slovak center between years 2002-2018 were evaluated in a retrospective study. The mean age was 55.8 years (range 22-77 years). Median of follo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…Both TKIs cause hypertension in up to 47% of patients, which is probably due to inhibition of the VEGF signaling [ 4 ]. In another study, 14% of patients with nilotinib treatment have one or more cardiovascular events, including peripheral artery disease (10%) and myocardial infarction (4%) [ 5 ]. Ponatinib is associated with a significant incidence of arterial occlusion events (26%) [ 6 ] and other adverse cardiac events, including arrhythmia, hypertension, and myocardial infarction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Both TKIs cause hypertension in up to 47% of patients, which is probably due to inhibition of the VEGF signaling [ 4 ]. In another study, 14% of patients with nilotinib treatment have one or more cardiovascular events, including peripheral artery disease (10%) and myocardial infarction (4%) [ 5 ]. Ponatinib is associated with a significant incidence of arterial occlusion events (26%) [ 6 ] and other adverse cardiac events, including arrhythmia, hypertension, and myocardial infarction [ 7 ].…”
Section: Introductionmentioning
confidence: 99%
“…Another study showed that 7.5% of patients treated with nilotinib developed acute coronary syndrome, among whom two patients had acute myocardial infarction and one patient died ( 34 ). In another single-center retrospective study that also demonstrated nilotinib-associated cardiovascular toxicity, Petrikova et al ( 35 ) evaluated cardiovascular events in 82 patients with CML who received nilotinib or imatinib. In the nilotinib group, 14% of patients had one or more cardiovascular events, with myocardial infarction accounting for 4% of all events ( 35 ).…”
Section: Chemotherapeutic Drugsmentioning
confidence: 99%
“…In another single-center retrospective study that also demonstrated nilotinib-associated cardiovascular toxicity, Petrikova et al ( 35 ) evaluated cardiovascular events in 82 patients with CML who received nilotinib or imatinib. In the nilotinib group, 14% of patients had one or more cardiovascular events, with myocardial infarction accounting for 4% of all events ( 35 ). The effects of sunitinib and sorafenib on tumor-associated endothelial cells may also lead to the activation of systemic coagulation in patients with cancer, making them more susceptible to thromboembolism.…”
Section: Chemotherapeutic Drugsmentioning
confidence: 99%